(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Digestion is a main process of human body. Food is essential for body and digestion, conversion of foodtakes place in digestive tract.AnnavahaSrotasDushti leads to indigestion, anorexia, lack of interest towardsfood which leads to Anorectic disorders like Arsha,Parikartika etc.Contrarily this seems to be an increasingincidence of the commonest of all anal disease, i.e. Haemorrhoids and fissure in ano. Though Sushrutahasdescribed detailed of, however as lifestyle has been changed significantly therefore it is of great importanceto study other causes of Haemorrhoids according to modern era. Hence, the diseases of ano-rectal area arethe commonest of all the diseases of GI tract. This study aimed at Annavahsroto-dushti and its relationin Pathogenesis of ArshaVyadhi and its management.They were well known for time immemorial to thephysician and surgeon due to the worldwide distribution and trouble caused by them.